INFLUENCE OF THE AROMATIC POLYMERIC MATRIX TYPE ON STABILITY OF NANOSIZED PALLADIUM CATALYSTS IN SUZUKI REACTION - E.S. Bakhvalova (Физико-химические аспекты изучения кластеров, наноструктур и наноматериалов, 2020)
This work is devoted to the study of the influence of the type of polymeric matrix of hyper-crosslinked polystyrene on activity and stability of palladium catalysts of Suzuki cross-coupling. The use of the hyper-crosslinked polystyrene functionalized with tertiary amino groups was shown to be promising in terms of ensuring of the catalyst stability during recycles, but in order to achieve 100 % conversion of aryl halide ( 4 - bromanisole) the use of strong excess of phenylboronic acid and of a base is required. The catalyst based on non-functionalized hyper-crosslinked polystyrene had higher activity and allowed achieving complete conversion of 4 - bromanisole during the reaction under mild conditions ( 70°С, ethanol and water mixture is in the ratio of 5:1 as a solvent) while using 1,5 - fold excess of phenylboronic acid. However, strong adsorption of the cross-coupling product in a hydrophobic polymeric matrix was found to be a disadvantage of such a system.